SOCIOLINGUISTIC DIMENSIONS OF SPOUSAL COMMUNICATION IN BUCHI EMECHETA’S SECOND-CLASS CITIZEN AND AKACHI ADIMORAEZEIGBO’S THE LAST OF THE STRONG ONES (2017)
Spousal communication, a feature of language, which unravels certain sociolinguistic characteristics of a husband and his wife, is a dominant feature of African novels by female writers. Previous studies on Emecheta and Adimora-Ezeigbo were theme-based, with little attention paid to spousal communication in their novels. This study investigated the dimensions of husband-wife linguistic and paralinguistic practices in two select novels of Emecheta and Adimora-Ezeigbo, with a view to identifying the influences of indigenous culture on spousal communication. Hymes‟ Ethnography of Communication, and Hudson-Weems‟ Womanism, which explores the relationship between social and cultural meanings, and the natural contributions of women to society, were adopted accordingly. Emecheta‟s Second-Class Citizen (SCC) and Adimora-Ezeigbo‟s The Last of the Strong Ones (LSO) were purposively sampled because of their thematic preoccupation with spousal communication. Data were subjected to sociolinguistic analysis. Spouses‟ linguistic and paralinguistic behaviour portray the influence of the African culture. Spousal communication takes place among seven couples: Francis and Adah in SCC; Obiatu and Ejimnaka, Omeozo and Onyeka, Okorie and Ngbeke, Iheme and Chibuka, Iwuchukwu and Chieme, and Aziagba and Okoroji in LSO. Among the dimensions of interaction common to the two novels are solidarity, dispute, respect, reconciliation, disregard, intimacy, family planning, identification, criticism and abusive remarks. While financial dispute appeared in SCC, it is not present in LSO. Both authors use personal pronouns to describe the solidarity between the spouses, and explore the use of first and second person singular to demonstrate how a husband influences his wife into submission. Expressions of affection in the use of possessive pronouns, such as, “my” in “my wife”, “my mother” and “oyoyo M” (my beauty) are used for reconciliation in both novels. While Ezeigbo uses Obiatu‟s “look of great affection” and Ejimnaka‟s “gaze without blinking” as part of paralinguistic features to demonstrate intimacy between the couples in LSO, Emecheta uses “disregard” as a conventional paralinguistic feature, which spouses use to deny, insult, question or challenge each other in SCC. Periphrasis, which is a non-hostile verbal communication, is used in the expression of family planning dispute in SCC. Gender roles are well defined for spouses in LSO. Emecheta employs respect to depict the social roles of a wife as a mother to both husband and children. The husbands assume an air of superiority and power, and create for their wives inferior status in SCC and LSO, thereby displaying the influence of patriarchal African culture. Aziagba‟s leading role in her relationship with Okoroji is an exception in LSO. The presence of Christianity, education and other forms of foreign culture reversed the roles assigned to spouses in SCC as reflected in Adah. Rhetorical devices, such as lexical borrowing, codemixing and code-switching permeate the novels to foreground the use of the English Language in an African society. Spousal communication portrays patriarchal domination and plays a significant role in showcasing salient aspects of African culture in Second-Class Citizen and The Last of the Strong Ones. There is the need to acknowledge African worldviews from which spouses draw their communicative practices. Keywords: Spousal communication, Emecheta and Adimora-Ezeigbo‟s novels, African Culture, Speech acts, Linguistic and paralinguistic behaviour. Word count: 498